The Cuban immigration of 1980: a special mental health challenge. - Silver, L B (1985)
The 124,769 Cubans who entered the United States from Cuba in a boatlift in 1980 included a small minority of people who needed mental health care. Some had been taken involuntarily from psychiatric hospitals, mental retardation facilities, jails, and prisons. The National Institute of Mental Health, Public Health Service (PHS), was responsible for mental health screening, evaluation, and treatment of the Cuban Entrants. Bilingual psychiatrists and psychologists found that many Entrants given preliminary evaluations showed evidence of transient situational stress reactions, not psychiatric illnesses. Entrants who had not yet been sponsored were consolidated into one facility in October 1980, and about 100 of those with severe problems were transferred to an Immigration and Naturalization Service-PHS evaluation facility in Washington, DC. Between March 1, 1981, and March 1, 1982, a total of 3,035 Entrants were evaluated at both facilities. Among the 1,307 persons who presented symptoms, there was a primary diagnosis of personality disorders for 26 percent, schizophrenic disorders for 15 percent, adjustment disorders for 14.5 percent, mental retardation for 8.6 percent, chronic alcohol abuse for 8.6 percent, and major depression for 7.2 percent. Only 459 Cubans with symptoms were found to be in need of further psychiatric care. As of October 1984, many Entrants with psychiatric illnesses remained under inpatient or community-based halfway house psychiatric care as a direct Federal responsibility. A PHS program for further placement in community-based facilities is underway.